EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT ON PERFORMANCE OF MOBILE TELECOMMUNICATION NETWORK, ABUJA, NIGERIA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
According to this study on how customer relationship management affects performance, the majority of companies in fiercely competitive industries, such as the telecom sector in developing nations, continue to downplay the significance of maintaining a customer-centric focus, which should give them the competitive edge they need to continuously improve performance. Therefore, it looked at how MTN, Nigeria's performance in Abuja, Federal Capital Territory, was affected by customer relationship management. 395 workers from various offices participated in the survey. An adjusted sample size of 219 was determined after the study followed Yamane's simple methods for determining sample size. Stratified, purposive, and random sampling techniques were used to present a well-structured questionnaire to this sample size. Simple percentage (%) statistical methods were used to examine the collected data. ANOVA and multiple regression analysis were used to examine the hypotheses. According to the report, during the study's time frame, customer relationships management had a major effect on organizational performance in the Nigerian Federal Capital Territory's telecom sector. As a result, it suggested, among other things, that management, shareholders, and owners of various businesses, regardless of size, should constantly work to implement the best customer relationship management index that would enhance particular organizational performance metrics as identified in this study.